The principle of publicity and the right to privacy in cases with sexual offence being the issue of the penal proceedings. Comparative approach - Konca, Paulina (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
The article concerns a conflict between the right to privacy and the principle of external publicity, including some other principles of criminal procedure in terms of cases with a sexual offence being the issue of the proceedings. The author presents the Polish regulations against the background of the Spanish ones and refers to social campaigns and solutions that function in other European countries in order to demonstrate both the importance of the victim’s dignity and right to privacy protection in view of preventing the secondary victimization. She also tries to show the mechanisms ensuring such protection. Moreover, the author analyses the issue of the defendant’s right to privacy protection. Because the principle of external openness is closely related to the access of the media to a trial, the article also focused on the radio and television reporting in the context of new media development with a particular emphasis on matters involving public figures.